The Effect of Bone Marrow Transplantation on Oocyte-Granulosa Cell Interaction and Follicular Development of Cisplatin-Induced Ovarian Failure in Rat - hendi hendarto (Journal of Stem Cell Research and Tissue Engineering, 2021)
Introduction: Chemotherapy has cytotoxic effect that induces follicular damage and abnormal folliculogenesis leads to ovarian failure. Two crucial   growth factors in abnormal folliculogenesis, Growth Differentiation Factor-9 (GDF-9) and Kit-Ligand, will be disrupted and affect follicular development. In this study, we evaluate whether bone marrow transplantation (BMT) has a role on oocyte-granulosa cell interaction by analyzing GDF-9 and Kit-Ligand expressions and also follicular development by analyzing primordial, primary, secondary and graafian follicles of cisplatin-induced ovarian failure in rat. Material and method: Forty eight rats were divided into three groups: control, cisplatin and cisplatin + BMT. Ovarian failure was induced by administration   of intraperitoneal cisplatin 5 mg/kg body weight for 1 week. BMT 2 x107 cells were injected through rat tail vein after cisplatin administration.  Bone marrow was isolated from rat femur and characterized    by CD44(+), CD45(-), CD105(+). Immunohistochemistry examinations for ovarian GDF-9, Kit-Ligand and follicle development evaluation were performed after 2 weeks of BMT injection. Results:  The  expressions   of Kit-ligand  among  three  groups  by ANOVA were  significant different (p=0.00), whereas by Post Hoc: cisplatin group lower  than  control  group (p=0.00); cisplatin + BMT group  higher than  cisplatin group (p=0.00); and no significant different between  control  group and cisplatin + BMT group (p=0.955). The expressions of GDF-9 by Kruskal Wallis showed significant different (p=0.00) among three groups whereas cisplatin + BMT group higher than cisplatin group and control group. In cisplatin + BMT group the number of primordial, primary, secondary and graafian follicles were higher than those in cisplatin group; but were lower than those in control group (p=0.000). Positive Paul Kart Horan (PKH) labeling was seen in cisplatin + BMT   group only. Conclusion:  In cisplatin-induced ovarian failure in rat, bone marrow transplantation may improve oocytegranulosa cell interaction and follicular development.